First record of the Paleozoic land snail family Anthracopupidae in the Lower Jurassic of China and the origin of Stylommatophora. (March 2020) - Jochum, Adrienne; Yu, Tingting; Neubauer, Thomas A.
Abstract: Computed tomographic (CT) imaging allows new accessibility to shells of gastropod fossil taxa and their extant relatives, providing new data for interpreting former systematic assignments. The highly questionable ellobiid assignment of the nonmarine gastropod genus Protocarychium Pan, 1982 from the Lower Jurassic of Hunan, China, is reevaluated using CT imaging to assess internal aspects of the shell. By comparing these new data to those of stylommatophoran, ellobiid, and caenogastropod clades in the literature, this work reveals that Protocarychium bears no affinity to the Carychiidae, which are otherwise known only from the Cenozoic, but rather to the Paleozoic land snail family Anthracopupidae Wenz, 1938. This finding constitutes the first Asian appearance of anthracopupid snails beyond their known North American and European range. Contrary to the current opinion, we suggest the Anthracopupidae to be a basal stylommatophoran clade, which places the origin of Stylommatophora at least in the late Carboniferous.